Odpowiedź :
a)
[tex] \frac{4}{5} + \frac{1}{10} = \frac{8}{10} + \frac{1}{10} = \frac{9}{10} [/tex]
b)
[tex] \frac{1}{6} + \frac{2}{3} = \frac{1}{6} + \frac{4}{6} = \frac{5}{6} [/tex]
c)
[tex] \frac{2}{3} + \frac{1}{5} = \frac{10}{15} + \frac{3}{15} = \frac{13}{15} [/tex]
d)
[tex] \frac{4}{7} + \frac{1}{2} = \frac{8}{14} + \frac{7}{14} = \frac{15}{14} = 1 \times \frac{1}{14} [/tex]
e)
[tex] \frac{8}{9} - \frac{1}{3} = \frac{8}{9} - \frac{3}{9} = \frac{5}{9} [/tex]
f)
[tex] \frac{3}{10} - \frac{1}{5} = \frac{3}{10} - \frac{2}{10} = \frac{1}{10} [/tex]
g)
[tex] \frac{4}{5} - \frac{2}{3} = \frac{12}{15} - \frac{10}{15} = \frac{2}{15} [/tex]
h)
[tex] \frac{5}{7} - \frac{1}{4} = \frac{20}{28} - \frac{7}{28} = \frac{13}{28} [/tex]
i)
[tex]2 \times \frac{2}{5} + 3 \times \frac{1}{2} = \frac{12}{5} + \frac{7}{2} = \frac{24}{10} + \frac{35}{10} = \frac{59}{10} = 5 \times \frac{9}{10} [/tex]
j)
[tex]4 \times \frac{3}{7} + 2 \times \frac{2}{3} = \frac{31}{7} + \frac{8}{3} = \frac{93}{21} + \frac{56}{21} = \frac{149}{21} = 7\times \frac{2}{21} [/tex]
k)
[tex]2 \times \frac{3}{8} + 1 \times \frac{1}{6} = \frac{19}{8} + \frac{7}{6} = \frac{57}{24} + \frac{28}{24} = \frac{85}{24} = 3 \times \frac{13}{24} [/tex]
l)
[tex]4 \times \frac{1}{2} + 2 \times \frac{3}{5} = \frac{9}{2} + \frac{13}{5} = \frac{45}{10} + \frac{26}{10} = \frac{71}{10} = 7 \times \frac{1}{10} [/tex]
m)
[tex]4 \times \frac{1}{4} - 2 \times \frac{2}{3} = \frac{17}{4} - \frac{8}{3} = \frac{51}{12} - \frac{32}{12} = \frac{19}{12} = 1 \times \frac{7}{12} [/tex]
n)
[tex]5 \times \frac{1}{9} - 1 \times \frac{5}{6} = \frac{46}{9} - \frac{11}{5} = \frac{230}{45} - \frac{99}{45} = \frac{131}{45} = 2 \times \frac{41}{45} [/tex]
o)
[tex]3 \times \frac{1}{15} - 1 \times \frac{1}{10} = \frac{46}{15} - \frac{11}{10} = \frac{92}{30} - \frac{33}{ 30} = \frac{59}{30} = 1 \times \frac{29}{30} [/tex]
p)
[tex]5 \times \frac{5}{13} - 3 \times \frac{1}{2} = \frac{70}{13} - \frac{7}{2} = \frac{140}{26} - \frac{91}{26} = \frac{49}{26} = 1 \times \frac{23}{26} [/tex]